2022
DOI: 10.1172/jci.insight.155010
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx heparan sulfate cleavage promotes endothelial cell angiopoietin-2 expression by impairing shear stress–related AMPK/FoxO1 signaling

Abstract: Angiopoietin-2 (Ang-2) is a key mediator of vascular disease during sepsis, and elevated plasma levels of Ang-2 are associated with organ injury scores and poor clinical outcomes. We have previously observed that biomarkers of endothelial glycocalyx (EG) damage correlate with plasma Ang-2 levels, suggesting a potential mechanistic linkage between EG injury and Ang-2 expression during states of systemic inflammation. However, the cell signaling mechanisms regulating Ang-2 expression following EG damage are unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
3
12
0
Order By: Relevance
“…This is in line with the perception that the endothelial glycocalyx serves as a key factor in maintaining homeostasis of the vascular endothelium (35,36). Even though a causal relationship cannot be established from our data, some evidence suggests that glycocalyx damage at least precedes impaired endothelial function as Richter et al showed that in septic children and in mouse models of sepsis, heparan sulfate levels peak prior to Ang-2 levels (37). Elevated Ang-2 concentrations have been associated with increased albuminuria which is associated with impaired pulmonary and renal function (38, 39).…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with the perception that the endothelial glycocalyx serves as a key factor in maintaining homeostasis of the vascular endothelium (35,36). Even though a causal relationship cannot be established from our data, some evidence suggests that glycocalyx damage at least precedes impaired endothelial function as Richter et al showed that in septic children and in mouse models of sepsis, heparan sulfate levels peak prior to Ang-2 levels (37). Elevated Ang-2 concentrations have been associated with increased albuminuria which is associated with impaired pulmonary and renal function (38, 39).…”
Section: Discussionsupporting
confidence: 91%
“…Persistent damage to the EG, likely due to both ongoing shedding as well as transcriptional down-regulation of glycocalyx components, is reported in trauma and other critical illness states (45,(75)(76)(77)(78). An increase in succinate metabolism has been reported to drive transcriptional alterations (31,56) in several cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Activated leukocytes secrete soluble factors that can directly disrupt paracellular vascular endothelial cadherin linkages. Furthermore, recent data from Richter et al 25 demonstrate that heparan sulfate cleavage upregulates EC production of angiopoietin-2, resulting in suppression of Tie2 receptor–mediated maintenance of intercellular junction protein expression.…”
Section: The Endotheliopathy Of Traumamentioning
confidence: 99%